DRIVE CAMPAIGNS: "ANTI-SHARING IMAGES/PHOTOGRAPHS HARASSING WOMEN ON INSTANT MESSAGING APPS PHONE VISITING - Wardani, Winny Gunarti Widya (ADI Journal on Recent Innovation (AJRI), 2020)
The presence of cross-platformmessaging apps on smartphone allows people to instantly share information and images/photos. However, the development of this information technology also opens opportunities for the spread of gender-based of images/photos that tend to harass women. The act of harassing women through images/photos, whether producing or sharing them can be categorized as a violation of the law, as regulated in Law of the Republic of Indonesia No. 7 year 1984 on the Ratification of the Convention on the Elimination of All Forms of Discrimination against Women. This study focuses on the importance of campaign of"Anti-sharing images/ photos that harassed women in instant messaging apps on smartphone? as a form of social and cultural responsibility in the community. Qualitatively, the discussion uses the theory of design sociology as a solution to solve problems through campaign media. The results of this study discussions are expected to build public awareness to stop sharing habits or create images /photos that harass women, and invite people to jointly fight it.